IMPLEMENTATION OF AUTOMATIC GARBAGE BIN USING LINE FOLLOWER ROBOT BASED ON ARDUINO UNO MICROCONTROLLER METHOD - Dimar Pateman; Neng Cahya Ningsih; Rizky Adin Adriansah; Dhea Maulida Rahma (Jurnal Teknik, 2023)
A line follower robot-based automatic garbage collection system with Arduino Uno has been developed to improve efficiency and convenience in garbage collection. This system uses a robot controlled by Arduino Uno and equipped with sensors to identify and collect garbage automatically. A line follower robot is a robot that can follow a predetermined path. In this system, the predetermined path is a path that has been equipped with black lines as a guide for the robot. The robot is equipped with an infrared sensor to detect the black lines and follow the path precisely. The system is also equipped with a garbage sensing sensor attached to the robot. These sensors use technologies such as ultrasonic sensors or infrared sensors to detect the presence of garbage around the robot. When trash is detected, the robot will stop its movement and use a mechanical hand or suction system to pick up the trash. Arduino Uno acts as the main brain of this system. The Arduino Uno microcontroller controls the robot's movement based on inputs from the sensors installed. In addition, the Arduino Uno also manages the interaction with the garbage sensing sensors, processes the sensor data, and makes the necessary decisions for efficient garbage collection. The implementation of this system uses the Arduino platform and electronic components that are easy to find and affordable. Thus, this system can be implemented at an affordable cost and easy to develop. With this line follower robot-based automatic garbage can, it is expected to increase efficiency and convenience in garbage collection. This system can reduce human intervention in the waste collection process, reduce the time and effort required, and promote better and more efficient waste management.